The association between attention deficit/hyperactivity disorder and internet addiction: a systematic review and meta-analysis - Wang, Bing-qian; Yao, Nan-qi; Zhou, Xiang (BMC psychiatry, 2017)
This study aimed to analyze the association between Attention Deficit/Hyperactivity Disorder (ADHD) and Internet addiction (IA).
Gesehen am 20.11.2018